Pengaruh Kinerja Keuangan, Ukuran Perusahaan dan Internet Financial Reporting Terhadap Harga Saham Pada Perusahaan Telekomunikasi yang Terdaftar di Bursa Efek Indonesia - Ni Kadek Mutiara Sari; I Putu Julianto (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
Abstract This study was aimed to determine the effect of financial performance, firm size and Internet Financial Reporting (IFR) toward stock prices in telecommunications companies listed on the Indonesia Stock Exchange. Aspects of financial performance used in this study were associated with financial ratios in the form of Return on Asset (ROA), Debt to Equity Ratio (DER) and Current Ratio (CR). This type of research was quantitative research. The sample of this study was determined by using a purposive sampling technique with criteria for determining the sample, namely telecommunication companies listed on the Indonesia Stock Exchange during the 2018-2020 period, companies that have annual reports and sustainability reports for the 2018-2020 period and companies that have official company websites, in order to obtain sample data of 10 companies. Then, the data was analyzed by multiple linear regression analysis using SPSS 26 application. The results showed that ROA, DER, CR, firm size and IFR had an effect on stock prices. Keywords: Financial Performance, Firm Size, IFR, Stock Price